“Simultaneous determination of some water soluble vitamins in multivitamin preparations by high performance liquid chromatography”. - Umaru, Farouk Adams (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Science,